Development and implementation of an agricultural safety consultation program to protect dairy farm workers. (7th October 2012) - Keifer, M; Magurany-Brotski, C; Guerrero-Silva, F; Ellis, T
Abstract : Background: Dairies in Wisconsin, America's Dairyland, were caught unprepared in summer, 2011 when the State's Federal Occupational Safety and Health Administration (OSHA) announced it planned inspections and enforcement on dairies across the state. In Wisconsin, all work deaths dropped from 2009–2010, but agricultural deaths increased 66%, accounting for 32 of 91. OSHA is prohibited by Congress from enforcing on any agricultural operation with <11 non-family workers. However, dairy operations have grown. The National Farm Medicine Center developed the Agricultural Safety Consulting (ASC) service to assist the industry to improve safety and prepare for inspections. Our initial findings are presented. Objective: Describe findings of safety consulting on Wisconsin Dairies. Methods: ASC hired a career dairyman, a safety professional and a translator. Walkthroughs produced recommendations on safety changes and worker training. Data were collected on categorical hazards. Results: Major findings from nine large include: Average of 19.3 hazard findings in 31 hazard categories. Most common: lack of mobile equipment training (19), lack of fall protection (17), inadequate fixed machine guarding (15), unaddressed electrical hazards (10), missing hazard communication plans (9), confined space hazards (8), lack of required injury records (8), livestock handling issues (7). Contribution to the Field: Few Wisconsin farms have safety expertise. Farm Safety specialists are rare in the US. Training agricultural experts in safety and safety experts in agriculture produces a strong complimentary team. ASC provides safety consulting which can be coupled with research projects aimed at improving health and safety researchers and often cautious farm owners.